Síntese, caracterização e avaliação ecotoxicológica de nanocompósito de Ag3VO4/Ag - Cruvinel, Guilherme Henrique (Universidade Federal de São Carlos, 2023)
Historically, the development of new methods of synthesizing materials has been linked to the development of societies, mainly due to the ability to promote changes in materials and enable new types of technological applications. Although there is quite sophisticated content about pulsed laser in femtoseconds, there is still a need to understand the mechanisms of formation and transformation of semiconductor materials, as well as to verify the changes provided, in a more appropriate way, when synthesized by this technique. However, such development must always be combined with the need to minimize and verify nvironmental effects. This study had as main objectives to synthesize Ag3VO4 via microwave-assisted hydrothermal method, in different synthesis times (t: 2, 4, 8, 16, 32, 64 min); irradiate the Ag3VO4 samples using a pulsed laser in femtoseconds to form the composite; characterize particulate composites; as well as to evaluate the ecotoxicity of the composite on the floating aquatic macrophyte species Ricciocarpus natans. The powders obtained from the composites were structurally characterized by the techniques of X-ray diffraction, Raman scattering spectroscopy and UV-Vis electronic spectroscopy, and had the surface characterized by scanning and transmission electron microscopy techniques, allowing the identification of structural alterations and surface. Theoretical calculations were used to understand the geometric, vibrational, electronic and charge distribution structures at the atomic level, as well as the nature of chemical interactions present in semiconductor structures. In addition, toxicity bioassays were carried out until the 42nd day in order to obtain an analysis of the ecotoxicological effects, with the aid of mathematical modeling, of these particles on the bioindicator Ricciocarpus natans. The results showed that the synthesis time did not change the short, medium and long range in Ag3VO4. Irradiation of Ag3VO4 by pulsed laser in femtosecond promotes its decomposition into AgVO3 and metallic Ag, which allowed the formation of a nanostructured composite. The results indicated that all chemical bonds can be classified as transient type; chemical bonds between Ag and O atoms may be weaker than between V and O atoms; Unexpected chemical interactions between anions and between cations can occur in both semiconductors. The results of the bioassays indicated that adding twice the reference concentration and inhibiting the penetration of electromagnetic radiation in the system of this work contributed to cause changes in the average area occupied by aquatic plants.
Synthesis, characterization and ecotoxicological evaluation of Ag3VO4/Ag nanocomposite
Keywords: Ag3VO4; Laser pulsado em femtosegundos; Nanocompósito de prata; Avaliação ecotoxicológica; Método hidrotérmico assistido por micro-ondas; Femtosecond pulsed laser; Silver nanocomposite; Ecotoxicological evaluation; Microwaves assisted hydrothermal method; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA